Pelatihan Ketentuan Nilai Lain sebagai Dasar Pengenaan Pajak dan Besaran Tertentu Pajak Pertambahan Nilai - Susanna Hartanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The 12% Value Added Tax increase came into effect in 2025. To cancel the rise in the Value Added Tax rate from 11% to 12%, the government finally took the method of not issuing a new Law, but with the new Value Added Tax calculation mechanism while still increasing the rate to 12 percent. Training on provision of other value as the tax base and certain amount of value added tax was a community service program conducted. It aimed to enhance the knowledge and understanding of new regulation in value added tax as lots of taxpayers are still confused with the implementation of the new regulations. The method used in this community service is online webinars using four stages  to implement the community service event. The results of this project are expected to give benefits for taxpayer in understanding the new regulations. The findings confirmed that Community service activities can be said to be successful with the increase in knowledge and understanding of taxpayers regarding the new regulation in value added tax. Further socialization or face-to-face tax training is needed to provide assistance to taxpayers in implementing value added tax reporting correctly, completely, and on time.